A survey of accessibility and utilisation of chiropractic services for wheelchair-users in the United Kingdom: What are the issues? - McKay Naomi D; Langworthy Jennifer (Chiropractic & Manual Therapies, 2011)
Abstract Background People with physical disabilities experience barriers to healthcare across all services despite a legal and moral obligation to the contrary. Complementary medicine is considered as supplementary to conventional care and integration of these approaches is essential to achieve optimal care. This paper explores the utilisation of chiropractic services and practitioner experiences of treating wheelchair-users which appears under-reported. Methods A 20 item questionnaire was posted to 250 randomly selected chiropractors registered with the General Chiropractic Council. Follow-up questionnaires were sent 7 days after the initial return date. Quantitative data were subjected to frequency analysis. Results The response rate was 64% (n = 161). The majority (66%) of chiropractors had been in practice less than 10 years and were practice owners (50%). Fifty-two percent of chiropractors sampled had treated a patient in a wheelchair in the previous 5 years. The majority (87%) had treated between 1 and 5 such patients. Patients with multiple sclerosis, stroke and cerebral palsy most commonly presented for treatment. The majority of patients' presenting complaint was musculoskeletal in origin, primarily for pain control. Only 13% of respondents worked in a fully accessible clinic. Impracticality of alterations was the most common reason for inaccessibility. Conclusions Wheelchair-users seem to be an underserved patient group in relation to chiropractic services. Chiropractic management is primarily utilised for pain control in patients with physical disabilities in which mobility may be improved or maintained. Co-management of wheelchair-users with GPs appears to be desirable in order to achieve optimal patient care however more research is required regarding the efficacy of chiropractic treatment for a range of disabling conditions. Physical access was identified as a key barrier to accessing care.